Enyne- and enediyne-y-lactonefrso m the bark of Meiogyne cylindrocarpa - Awang, Khalijah; Bousseroul, H.; Guéritte, F.; Litaudon, M. (Elsevier, 2012)
The chemical investigation ofthe EtOAc extract ofthe bark ofMeiogrne qilindrocarpa led to the isolation of two enyne- and five enediynel-lactones, sapranthins A-G (1 -7), of which six were new. They were identified by mass spectrometry,extensive one- and two-dimensional NMR spectroscopya nd through comparison with data reported in the Iiterature.S apranthinsB , C and E (2,3 and 5, respectively showed a weak cytotoxic activity on L1210 with lC50 values comprised between 8.1 and 18.0 µM.